The Opinions of the School Administrators and Teachers on the Education Given to Gifted and Talented Students in the Resource Room - LEVENT, AHMET FARUK (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2019)
The purpose of this study was to examine the opinions of school administrators and teachers on the education given to gifted and talented students in the resource room. The data of this study, which was conducted with qualitative research methods in a case design, was obtained by face-to-face interview using a semi-structured interview form. 20 school administrators and 19 teachers were interviewed. The data obtained during the interviews were subjected to content analysis and coding was done. According to the findings of the study, the participant school administrators and the teachers stated that in the resource rooms, the students were usually given smart toys and game sand that no differentiated education could be given. Most of the participants stated that they lacked a specific curriculum and plan for the resource room and lack of material and lack of physical conditions. In addition, the participants pointed out the importance of in-service training for teachers by expressing that the factor of teachers is the determining factor in meeting the educational needs of gifted and talented students in the resource education rooms.
Keywords: Gifted students; gifted education; resource room; school administrator; teacher